The ABCG2 gene Q141K polymorphism contributes to an increased risk of gout: A meta-analysis of 2185 cases. Issue 5 (September 2014) - Qiu, Ya; Liu, Hua; Qing, Yufeng; Yang, Min; Tan, Xiaoyao; Zhao, Mingcai; Lin, Monica; Zhou, Jingguo
Abstract Objectives. Individual genetic association studies examining the relationship between the ABCG2 gene polymorphisms and gout have yielded inconsistent results. This study aims to evaluate the association between the ABCG2 gene variants and gout using meta-analysis. Materials and methods. Relevant studies were identified by searching databases extensively. The odds ratio (OR) was calculated using a random-effect or fixed-effect model. A Q statistic was used to evaluate homogeneity, and Egger's test and funnel plot were used to assess publication bias. Subgroup analyses on ethnicities and sex were also performed. Results. A total of 7 studies, including 2185 gout patients and 8028 controls from 5 countries or regions, were included and identified for the current meta-analysis. It was found that the A allele or AA genotype of the ABCG2 Q141K polymorphism (rs2231142) had an increased risk of gout in the general population (A allele, p < 0.00001 and AA genotype, p < 0.00001, respectively). On the contrary, CC homozygote played a protective role against the risk of gout (p < 0.00001). Similar results were found in subgroup analyses. However, there was a significant heterogeneity among studies. Conclusions. Existing evidence indicates that the Q141K polymorphism (rs2231142, the A allele and AA genotype) is associated with an increased risk of gout.